Types of Presupposition and Derivational Affix in the Novel Pride and Prejudice by Jane Austen - Syafaat, Muhammad; Saragih, Gustaman (Universitas Indraprasta PGRI, 2023)
The aim of the research is 1) to analyze and clarify types of presupposition found in the Novel Pride and Prejudice by Jane Austen. 2) to analyze derivational affixes found in Novel Pride and Prejudice by Jane Austen. The research method is descriptive qualitative. The data of this research is gained from the novel which found 40 data of presupposition and 50 data of derivational affix. Analysis is fulfilled with each of the utterance is divided and distributed into six kind of presupposition, and every word/base that contain derivational affix is divided and distribute to nine affixation process explained by tree diagram. The result of the research is the Existential Presupposition is the first mostused with amount 11 data out of 40 data. Existential Presupposition has 27,5% in dialogue. Verb to Noun is the most dominant derivational affix process with total 12 data out of 50 data getting 24% portion.